Application of near infrared spectroscopy and chemometrics for the analysis of nutraceuticals in South Africa - Van der Merwe, Sanette (Cape Peninsula University of Technology, 2019)
Thesis (Master of Applied Sciences in Chemistry)--Cape Peninsula University of Technology, 2018. === The high demand of omega-3 fish oil nutraceuticals (dietary supplements) is due to the numerous health benefits contributed by the polyunsaturated fatty acids (PUFA’s). The nutraceutical industry is required to follow good manufacturing practice (GMP) standards in order to ensure label claims and prevent adulteration. It is vital that the quality control (QC) procedures will be able to detect adulterated products. It is thus necessary to ensure the analytical techniques are adequate by using validated methods. The qualification or identification of natural fish oils is a difficult task due to overlapping concentration ranges of PUFA’s and other similar properties. Gas chromatography (GC) is the prescribed technique in the nutraceutical industry for analysis of omega-3 fatty acids, but it is time-consuming and costly. Near infrared (NIR) spectroscopy is a rapid and cost-effective technique that can replace the prescribed method if proven equivalent, through validation according to pharmaceutical criteria. In this study, NIR spectroscopy in combination with chemometrics was considered as an alternative method to GC, to identify various commercial fish oils and to quantify the PUFA’s. Identification methods were developed for nine commercial omega-3 fish oils using spectral libraries. Quantitative NIR methods were developed for arachidonic acid (AA), docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) in fish oils expressed as mg.g-1 as well as percentage (%) area using partial least squares (PLS) regression and independent validation by superimposing datasets with mutual properties. Based on the statistics in terms of SEC, R2, SEP and r of the PUFA models, the NIR method was equivalent to the prescribed GC methods and precision results obtained were within the prescribed criteria. NIR spectroscopy and chemometrics can be used for conclusive identification and quantification of omega-3 fish oils, thereby minimizing the risk of adulteration. The method also complied with the prescribed pharmaceutical method validation criteria; therefore, was demonstrated as an alternative method to GC for the nutraceutical industry.